2023
DOI: 10.1088/1755-1315/1158/4/042028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seedling Age and NPK Fertilization on Growth and Yield of Kohlrabi (Brassica oleracea var gongylodes) Planted in Gypsiferous Soil

Abstract: Kohlrabi (Brassica oleracea var. gongylodes) ‘White Vienna cv.’ was grown in the Experimental Station of the Department of Horticulture and Landscape in the College of Agriculture at Tikrit University in Salah al-Din, Iraq, during the winter of 2021–2022. The purpose of this research was to examine the impact of seedling age and NPK combinations on kohlrabi plant growth and yield. Most values for vegetative growth traits and yield were found to be highest for seedlings aged 45 days. Plant growth and yield were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
0
1
Order By: Relevance
“…In view of our results, the fact that aquaponic systems provide a lower amount of certain nutrients, such as potassium, phosphates, and mainly nitrates, negatively affects the growth and development of kohlrabi bulbs. These results coincide with the findings by Jamil [21] and Al-Azzawi et al [22] who observed a reduction in both dry matter and diameter of kohlrabi plants due to the application of deficient doses of nitrogen, phosphorus, and potassium, even observing that the combined application of organic and inorganic fertilizers increased these parameters. In our case, the extra contribution of inorganic fertilizers in the mixed water + S treatment provided concentrations of those nutrients that were quite similar to those of the control irrigation, diminishing the negative effects of the deficient treatment (mixed water).…”
Section: Physical Characterization Of Kohlrabi Bulbsupporting
confidence: 92%
See 1 more Smart Citation
“…In view of our results, the fact that aquaponic systems provide a lower amount of certain nutrients, such as potassium, phosphates, and mainly nitrates, negatively affects the growth and development of kohlrabi bulbs. These results coincide with the findings by Jamil [21] and Al-Azzawi et al [22] who observed a reduction in both dry matter and diameter of kohlrabi plants due to the application of deficient doses of nitrogen, phosphorus, and potassium, even observing that the combined application of organic and inorganic fertilizers increased these parameters. In our case, the extra contribution of inorganic fertilizers in the mixed water + S treatment provided concentrations of those nutrients that were quite similar to those of the control irrigation, diminishing the negative effects of the deficient treatment (mixed water).…”
Section: Physical Characterization Of Kohlrabi Bulbsupporting
confidence: 92%
“…On the contrary, other authors did not see significant differences in the content of phenolic compounds of Lactuca sativa L., neither by the application of different nitrogen concentrations nor by the application of PGPB [32]. However, as we observed in our plants irrigated with a water + S mixture, Shams [33] and Al-Azzawi et al [22] observed an increase in total phenolic compounds in kohlrabi plants when applying combined mineral and organic N. This higher content of total phenolic compounds is partly responsible for granting them a greater antioxidant potential, as these compounds protect against oxidative damage and play an important role in human nutrition. Therefore, this increase in total phenolic compounds is of great interest, as it has been observed that phenols act as excellent antiinflammatory agents, preventing diabetes mellitus and its possible complications [30].…”
Section: Total Phenolic Compounds and Antioxidant Activity (Abts + *)contrasting
confidence: 87%